Comparing a range of impellers for "stirring as foam disruption" - Boon, L; Hoeks, F; van der Lans, R; Bujalski, W; Wolff, M; Nienow, A (2002)
The effectiveness of a range of impellers for "stirring as foam disruption" (SAFD) is assessed in a vessel of 0.72 m diameter and an aspect ratio of 2: 1. Measurement of power drawn by the impeller achieving SAFD and of the three-dimensional flow field close to the dispersion surface are both used to explain the findings along with the global gas hold-up. A large radial flow Rushton turbine can disrupt foam at a great height but requires high power. Down-pumping hydrofoils are only effective when the ungassed liquid height is below the level of the impeller employed to disrupt foam. Up-pumping hydrofoils are the most effective because their flow pattern gives rise to high velocities across the dispersion surface, which are able to entrain foam in the downflow generated at the walls. © 2002 Elsevier Science B.V. All rights reserved.